Investigation of the effectiveness of Newcastle disease virus production in different bioreactors - Ja'afar, Ja'afar Nuhu (Kulliyyah of Engineering, International Islamic University Malaysia, 2009)
Newcastle Disease (ND) is a highly devastating poultry disease that sabotages economic growth. Currently, the traditional method of using egg in vaccine production is expensive, inconvenient to determine virus proliferation, time consuming, laborious and requires dozens of crates of egg but with low yields. The current concept of quality assurance of vaccines is less established with egg-based production. Furthermore, the relationship between freeze/thaw and sonication with respect to virus recovery is poorly documented. This study aimed at transferring the existing production process from egg to cell culture through the selection of a suitable host cell line that would sustain the fast replication of Newcastle disease virus (NDV) and the appropriate culture system that could augment maximum yield of the virus. Recovery of virus using freeze/thaw and sonication was also studied. First experiments of host cell selection for virus propagation in CEF, DF-1 and Vero cells were carried out in T-flask using both velogenic and lentogenic (AF2240 and F respectively) strains of NDV. Analysis was on fast adaptation and ethical values. As these experiments were successful, different culture media (DMEM F/12, DMEM, RPMI and MEM) selection based on cost, high viable cell concentration and virus yield was carried out using T-flask. Microcarrier selection (Cytodex 1 and 3, Hillex® and Plastic Plus®) for microcarrier culture was carried out using Spinner flask. Selection included Halal composition and high viable cell concentration. Different experiments for virus yield in different bioreactors (T flask, BelloCell, Spinner flask and Stirred tank bioreactor) were carried out using both AF2240 and F strain. Lastly, experiments generated using STATISTICA software, were carried out to examine the effect of freeze/thaw and sonication on virus recovery using a water bath sonicator. Vero cell became more adapted to AF2240 compared to other cell lines with HA titre of 2048 after three passages, but due to ethical concern, DF-1 was used. DMEM had the highest viable cell concentration with 1.25 ± 0.032 x 106 cells/ml, but could not yield high virus titre. RPMI, however, had a viable cell concentration of 8.10 ± 0.926 x 105 cells/ml and supported high titre of virus in addition to being more economical. Cytodex 3 had the highest viable cell concentration, 2.65 ± 0.201 x 105 cells/ml, but had a pig gelatin surface coating. Cytodex 1, however, had a viable cell concentration of 2.03 ± 0.217 x 105 cells/ml with no gelatin coating. Stirred tank and T-flask gave the highest HA titre of 128 using F strain of NDV. The HI titre of the propagated virus was 32 that was within the standards of OIE. One cycle of freeze/thaw, sonicating at medium amplitude for 1.5 minutes at water bath temperature of 15 oC had the highest virus recovered. The ability to produce antigenic NDV in stirred tank could be proposed to substitute the existing egg method of NDV vaccine production in the future.